2018
DOI: 10.1177/2010105818760923
|View full text |Cite
|
Sign up to set email alerts
|

Do peer support groups have an effect on medication adherence? A study among people living with HIV/AIDS in Enugu State, Nigeria

Abstract: Background: The health benefits of antiretroviral treatment greatly depend on the extent to which people living with HIV/ AIDS adhere to the prescribed daily dosing regimens. Peer support groups are expected to have a high impact on adherence to medication among people living with HIV/AIDS. Objectives: This study was designed to determine factors affecting adherence to medication among people living with HIV/ AIDS in peer support and non-support groups attending antiretroviral clinics in Enugu State, Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 22 publications
2
24
0
1
Order By: Relevance
“…Our findings confirm previous studies in Senegal, West Africa and in Uganda who have reported a similar pattern among HIV-positive patients [15-31]. Although other studies have reported mixed results regarding the role of marital status [32, 33] on adherence, this situation may be explained by the fact that single patients may have access to better social support as they may only share their status with the medical staff for HIV antiretroviral therapy. For widowed HIV positive patients, HIV/AIDS represents a shame and they may fear discrimination and reject from the community who may already know their HIV status.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirm previous studies in Senegal, West Africa and in Uganda who have reported a similar pattern among HIV-positive patients [15-31]. Although other studies have reported mixed results regarding the role of marital status [32, 33] on adherence, this situation may be explained by the fact that single patients may have access to better social support as they may only share their status with the medical staff for HIV antiretroviral therapy. For widowed HIV positive patients, HIV/AIDS represents a shame and they may fear discrimination and reject from the community who may already know their HIV status.…”
Section: Discussionsupporting
confidence: 90%
“…Measurements of adherence based on participant's self-reports over 28 days are open to recall bias. Peer support groups were formal meetings of PLHIV aged 18 or over, where discussions centred on identifying barriers to adherence and problem-solving solutions [59].…”
Section: General Adult Populationsmentioning
confidence: 99%
“…Studies that did not measure adherence as an outcome were excluded from the systematic review. Thirty-one journal articles met the inclusion criteria [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and were included in the systematic review. Figure 1 shows the flowchart of the systematic review process.…”
Section: Resultsmentioning
confidence: 99%
“…The study designs consisted of ten cohort studies [ 24 , 25 , 29 , 33 , 34 , 37 , 38 , 47 , 52 , 53 ], four pre-post studies [ 26 , 28 , 35 , 36 ], sixteen randomized controlled trials [ 27 , 31 , 32 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 54 ], and only one cross-sectional study [ 30 ].…”
Section: Resultsmentioning
confidence: 99%